Behavior of circular concrete columns reinforced with hollow composite sections and GFRP bars. (July 2020) - Alajarmeh, Omar; Manalo, Allan; Benmokrane, Brahim; Ferdous, Wahid; Mohammed, Ali; Abousnina, Rajab; Elchalakani, Mohamed; Edoo, Azam
Abstract: Hollow concrete columns (HCCs) constitute a structurally efficient construction system for marine and offshore structures, including bridge piers and piles. Conventionally, HCCs reinforced with steel bars are vulnerable to corrosion and can lose functionality as a result, especially in harsh environments. Moreover, HCCs are subjected to brittle failure behavior by concrete crushing due to the absence of the concrete core. Therefore, this study investigated the use of glass fiber-reinforced polymer (GFRP) bars as a solution for corrosion and the use of hollow composite-reinforced sections (HCRSs) to confine the inner concrete wall in HCCs. Furthermore, this study conducted an in-depth assessment of the effect of the reinforcement configuration and reinforcement ratio on the axial performance of HCCs. Eight HCCs with the same lateral-reinforcement configuration were prepared and tested under monotonic loading until failure. The column design included a column without any longitudinal reinforcement, one reinforced longitudinally with an HCRS, one reinforced longitudinally with GFRP bars, three reinforced with HCRSs and different amounts of GFRP bars (4, 6, and 8 bars), and three reinforced with HCRSs and different diameters of GFRP bars (13, 16, 19 mm). The test results show that longitudinal reinforcement—whether GFRP bars or HCRSs—significantly enhanced the strength and displacement capacities of the HCCs. Increasing the amount of GFRP bars was more effective than increasing the bar diameter in increasing the confined strength and the displacement capacity. The axial-load capacity of the GFRP/HCRS-reinforced HCCs could be accurately estimated by calculating the load contribution of the longitudinal reinforcement, considering the axial strain at the concrete peak strength. A new confinement model considering the combined effect of the longitudinal and transverse reinforcement in the lateral confinement process was also developed. Highlights: Compressive behavior of HCCs reinforced with Hollow Composite Section and GFRP bars. Effects of the different longitudinal reinforcement configurations. Effects of the amount and diameter of the longitudinal GFRP reinforcements. Evaluation of the failure mode, load-displacement, and load-strain of HCCs. Load capacity prediction of the HCCs with GFRP bars and Hollow Composite Section.